Lung cancer in older patients with granulomatosis with polyangiitis: a report of three cases - Malgorzata Potentas-Policewicz; Malgorzata Szolkowska; Katarzyna Blasinska; Dariusz Gawryluk; Malgorzata Sobiecka; Justyna Fijolek (BMC Pulmonary Medicine, 2024)
Abstract Background Granulomatosis with polyangiitis (GPA) is characterized by necrotizing granulomatous inflammation with necrotizing vasculitis predominantly affecting small to medium vessels. The survival rates have drastically improved; however, GPA can be lethal, with older patients having a worse prognosis and higher mortality than younger patients. Moreover, the incidence of various cancers has been reported to increase in patients with GPA. We aimed to discuss possible associations between GPA and lung cancer and emphasize the associated diagnostic challenges. Case presentation We encountered three older patients with chronic GPA who developed lung cancer during long-term follow-up. Two of the patients had a smoking history, with one having silicosis and the other having chronic obstructive pulmonary disease. Furthermore, all of them had radiation exposure from repeated radiography/computed tomography. All the patients had confirmed GPA, and vasculitis relapse was first suspected when new lung lesions were noted during follow-up. However, they had no new clinical symptoms, and serum ANCA titer increased only in one patient. All the patients received standard immunosuppressive treatment but eventually died. Conclusions Lung cancer is uncommon in patients with GPA; however, the similarity between the imaging findings of lung cancer and GPA may pose a diagnostic challenge. Clinicians should be particularly vigilant when treating older patients with an increased risk of cancer, as they are often asymptomatic or have poorly apparent clinical features.